Integrating conventional risk management and population models to assess risks from an established invasive freshwater fish. (15th December 2022) - Koehn, John D.; Stuart, Ivor G.; Todd, Charles R.
Highlights: Risk assessments are vital to invasive species control but not always suitable for natural resource managers. Integrating ISO likelihood and consequence risk assessments with population models provide a new approach. We apply and test this new method on the highly invasive common carp in Australia. This approach is widely applicable to invasive species globally.